Individual control of singlet lifetime and triplet yield in halogen-substituted coumarin derivatives. Issue 45 (21st July 2020) - Oberhofer, Katrin E.; Musheghyan, Mikayel; Wegscheider, Sebastian; Wörle, Martin; Iglev, Eleonora D.; Nikolova, Rositca D.; Kienberger, Reinhard; Pekov, Petko St.; Iglev, Hristo
Abstract : The photophysical properties of three 3-diethylphosphonocoumarin derivatives are studied by transient absorption spectroscopy and DFT calculations. Abstract : The photophysical properties of three 3-diethylphosphonocoumarin derivatives are studied by transient absorption spectroscopy and DFT calculations. The measured lifetime of the first excited singlet state changes upon halogen substitution at the 6-position from 40 ps for the unsubstituted compound to 100 ps for Cl and 24 ps for Br. This observation is in clear contradiction with the estimated singlet–triplet quantum yield, which increases with atomic weight of the substituted atom and is usually referred as a heavy-atom effect. The DFT calculations give evidence that the main reason for this behavior is the different composition of the HOMO, while the LUMO is similar for all three compounds. The optical excitation leads to intramolecular charge transfer from the halogen lone pairs to the π* molecular orbital and thus to a significant change in the molecular dipole moment. Hence, the latter phenomenon in combination with the heavy-atom effect enables an independent control of singlet lifetime and singlet–triplet quantum yield in the studied 3-diethylphosphonocoumarin derivatives.